Development and preliminary validation of the Clinician Affective REsponse (CARE) scale - Alberto Stefana; Paolo Fusar-Poli; Joshua Langfus; Eduard Vieta; Eric Youngstrom (Research in Psychotherapy, 2024)
The present study reports on the development and validation of the clinician affective response (CARE) scale. The CARE scale was designed as a self-report measure of therapists’ patterns of thoughts, feelings, and behaviors toward the patient during an individual psychotherapy session. An initial pool of 116 items was generated, and its quality was evaluated by subject matter experts. Validation data were gathered from licensed psychotherapists (n=554). We used exploratory factor analysis and item response theory-graded response modeling to select items, confirmatory factor analysis to test how well the factor structure fit the data, and k-fold cross-validation to ascertain the robustness of the model. Criterion validity was evaluated by correlating the scores of the scale with the characteristics of therapists, patients, and treatment. The selected model consists of 15 items and a 3-factor structure, which showed excellent model fit, good internal consistency, and evidence of criterion validity. The CARE scale, short and quick to complete, enables therapists to reflect on and recognize their inner experiences and quantify these experiences in ways conducive to statistical analysis and research. Furthermore, the monitoring of these affective reactions toward their patients can guide therapeutic interventions and inform clinical supervisors.